Penggunaan Media Pembelajaran Stacko Uno pada Mata Pelajaran Pendidikan Pancasila terhadap Minat Belajar Siswa: The Use of Stacko Uno Learning Media in Pancasila Education Subjects on Students' Learning Interests - Putri Intan; Fazli Rachman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Student learning interest in Pancasila Education subjects tends to be low due to learning methods that are still conventional and less interesting. To overcome this, innovative learning media are needed that can increase student participation and interest in the material. Stacko Uno is a game-based learning media designed to create a fun, interactive, and collaborative learning atmosphere. The purpose of this study was to determine the effect of using Stacko Uno media on the learning interest of eighth-grade students of SMPN 1 Nainggolan in the 2024/2025 academic year. This study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research subjects consisted of two classes, namely the experimental class that used Stacko Uno media and the control class that used conventional learning methods. The research instrument was a student learning interest questionnaire that had been tested for validity and reliability. Data were analyzed using the nonparametric Mann-Whitney U statistical test. The results showed that the Asymp. Sig. (2-tailed) value was <0.001. This value is smaller than the specified significance level (? = 0.05), so it can be concluded that there is a significant difference between students' learning interest in the experimental class using Stacko Uno media and the control class using conventional methods. The determination value shows that the use of Stacko Uno media influences 74.8% of the variation in learning interest. Thus, it can be concluded that the Stacko Uno learning media is effective in increasing students' learning interest in the Pancasila Education subject.